BUILDING RELIGIOUS AWERENESS THROUGH EDUCATIONAL TECHNOLOGY IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 - Hidayatulloh, Hidayatulloh; Nuraeni , Heni Ani (ANDRAGOGI, 2024)
The industrial revolution became a challenge for someone who could not take advantage of it and became an opportunity to change the growth mindset for productive thinkers. This research aims to discuss efforts to biild religious awareness through educational technology in the era of industrial revolution 4.0. This research will explore how technology can be used effectively to increase religious understanding and awareness at various levels of education, from elementary to highest levels. This research method uses library research using content analysis techniques. The research results to build religious awareness require three aspects: first, it requires integration between technology and religious values. Second, involving teachers and religious leaders in the use of educational technology. Third, providing broad access for all levels of society to educational technology. It is hoped that this research can serve as a guide for developing better religious education policies, as well as providing insight for educational practitioners, technology developers and the general public regarding the importance of technology in the Islamic religious context.